Development of an AC-DC boost power factor correction - Md Tahir, Zuraidi (2013)
With rapid development in power semiconductor devices, the usage of power electronic systems has expanded to new and wide application range that include residential, commercial, aerospace and many others. Power electronic interfaces such as switch mode power supplies have proved to be superior over traditional linear power supplies. However, their non-linear behavior puts a question mark on their high efficiency. The current drawn by the switch mode power supplies from the line is distorted resulting in a high Total Harmonic Distortion and low Power Factor. Power Factor, the ratio between the real or average power and the apparent power forms a very essential parameter in power system. It is indicative of how effectively the real power of the system has been utilized. With the stringent requirements of power quality, power factor correction has been an active research topic in power electronics, and significant efforts have been made on the developments of the power factor correction converters. This project aims to develop a circuit for power factor correction using active filtering approach by implementing boost converters arranged in parallel. It shall be based on an optimized power sharing strategy to improve the current quality and at the same time reduce the switching losses. The simulation result shows that the power factor was improved when the power factor corrector circuit added to the inverter and the power factor corrector circuit switching with proportional-integral-derivative controller shows better power factor then using pulse width modulation switching mode.